The effects of different iron shaft weights on golf swing performance - Yang, Chia-Chen; Chang, Che-Chia; Chao, Te; Tai, Hsia-Ling; Tsai, Yung-Shen (Frontiers in Bioengineering and Biotechnology, 2024)
This study examined the effects of three 7-iron shaft weights on golf swing performance among golfers of varying skill levels. The study included 10 low-handicap (LH; 4.3 ± 2.4) and 10 highhandicap (HH; 29.1 ± 5.4) right-handed golfers as participants. The participants were randomly assigned 7-iron clubs with shaft weights categorized as light (77 g), medium (98 g), or heavy (114 g), and they performed test shots. Kinematic data were captured using a motion analysis system with nine infra-red high speed cameras; a force platform connected to this system was used to record weight transfer patterns. Performance variables were assessed using a FlightScope launch monitor.A two-way mixed-design analysis of variance was used to determine the significance of the performance differences among both participant groups and golf shaft weights. The results indicated that during the backswing, the LH group exhibited significantly greater maximum rightward upper torso rotation, maximum X-factor, and maximum right wrist hinge rotation than did the HH group. During the downswing, the LH group exhibited significantly greater maximum upper torso angular velocity and maximum right wrist angular velocity than did the HH group.Moreover, the LH group produced significantly higher ball speeds, longer shot distances, and lower launch angles than did the HH group. The shaft weight neither greatly altered the golf swing nor displaced the center of gravity of the golfers. The lighter shafts were observed to facilitate faster clubhead speeds and initial ball velocities, thereby resulting in longer shot distances, especially among LH golfers. Although significant differences in swing mechanics and performance exist between HH and LH golfers, lighter shafts can contribute to increased shot distances for all golfers.